Management Information System; A Systematic Literatur Review - Nurmayuli, Nurmayuli; Arifin, Zulfan (Yayasan Putroe Ceudah Aceh, 2024)
Management Information System (MIS) is one of the important elements in various types of organizations including in educational institutions. This paper aims to explain the basic concepts of management information systems. This paper contains the understanding and components of management information systems, the scope of management information systems, and the benefits of management information systems. This paper is a type of research using PRISMA (Preferred Reporting Items For Systematic Review and Meta-Analysis) with identification, screening, eligebility, Inclouded. The search method is carried out on national literature using publish of perish (POP) with the database used, namely google scholar. The result of this paper is that the Management Information System (MIS) is to manage the information database and then shared with all stakeholders. The scope of Management Information System (MIS) refers to actually contained in three words that make it up, namely